FREQUENCY OF TOBACCO USE AND THE ATTITUDES OF HEALTH PROFESSIONS STUDENTS ON TOBACCO USE IN MONTENEGRO: GLOBAL HEALTH PROFESSIONS STUDENT SURVEY IN MONTENEGRO - Ramcilovic, Vilnerina; Catic, Sabina; Kujundzic, Enisa (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Health professionals play a significant role in advising patients on the harmful effects of tobacco on human health and on the ways of abandoning this bad habit. However, tobacco consumption is also a challenge for health professionals themselves, as well as for medical students. Aim: The objective of this study was to estimate the prevalence of smoking among students of health sciences in Montenegro, as well as to examine their attitudes related to tobacco control mechanisms. Methods: This is a secondary analysis of the Global Health Professions Student Survey, which was conducted by the Ministry of Health of Montenegro, in the period between October 2010 and March 2011. Results: In the 30 days preceding the survey, 25% of respondents had used tobacco. During the year preceding the survey, 38% smokers had consumed cigarettes on school premises. Of the respondents, 44.6% of smokers and 52.9% of non-smokers had been taught on the subject of the importance of providing educational material to patients, as a form of support to smoking cessation, but only 35% of smokers and 28% of non-smokers had received formal training on how to instruct patients to give up smoking. A total of 63.7% smokers and 81.7% non-smokers (p < 0.001) expressed the belief that health professionals who smoked cigarettes were less suited to advise patients on smoking cessation. There was a 72% lower probability that sixth year students would support the above stated attitude. Also, there was a 43% lower probability that the same attitude would be supported by students who felt that smoking in restaurants should not be banned in restaurants, and a 52% lower probability that this attitude would be supported by those students who believed that health workers do not need special training in smoking cessation techniques. Conclusion: The study showed that it was necessary to improve the curricula at health sciences faculties and improve formal training on the harmful effects of tobacco on human health, as well as to improve the training for acquiring evidence-based smoking cessation skills, which would have an indirect effect of reducing tobacco use among students.